RESEARCH OF STRUCTURE OF HYPOTHALAMIC NUCLEI OF ANIMALS BY METHODS OF FRACTAL GEOMETRY - Sergey L'vovich Molchatsky (Наука. Инновации. Технологии)
Theoretical justification of application of new physical approach to research of structure of lifeless and alive objects - a method of fractal geometry is given. It is shown that the brain of animals is a product of deeply nonequilibrium processes, and, therefore, object with fractional dimension. The technique of determination of fractal dimension (D) studied objects is offered. Results of the fractal analysis of computer images of microphotographs of the frontal cuts of supraoptic (SO) and are presented paraventricular (PV) nuclei of a hypothalamus of a cat. On the basis of the obtained data it is established that 1) the studied groups of neurones of area of each core have pronounced monofractal structure with different fractal dimensions; 2) therefore, each core in general is a multifractal.